Effect of Cryopreservation Conditions on Phenotypic Profile and Immunomodulating Activity of Fetal Liver Cells - Ostankov, Maksim V.; Leonova, Larisa A.; Bondarovich, Nikolay A.; Ostankova, Lyudmila V.; Goltsev, Anatolyi M. (Problems of Cryobiology and Cryomedicine, 2019)
The effect of cryopreservation conditions (concentration of dimethyl sulfoxide cryoprotector − DMSO, cooling rate in different temperature ranges) on phenotypic profile and immunomodulatory activity of rat fetal liver cells (FLC) of 14 days of gestation was investigated. The cells were frozen in two modes under the protection of 7.5; 10, and 12.5% DMSO. We evaluated the phenotypic profile of FLCs (CD34+CD38–, Sca-1+CD34-, Sca-1+CD34+, CD44-CD73+, CD44+CD73+), their cytomorphological indices, number and viability. The FLCs cryopreservation mode developed in this work ensured the preservation in a heterogeneous cell population with the immunomodulating activity, which was evaluated in the in vivo system on the model of experimental atopic dermatitis (EAD). The efficacy of using cryopreserved FLCs in mode 1 (1°С / min to –25°С; stabilization at –25°С for 5 min and plunging in liquid nitrogen) with 10% DMSO to restore blood parameters and reduce the intensity of skin inflammatory reactions in rats with induced EAD was experimentally established. Probl Cryobiol Cryomed 2019; 29(3): 266–276.